TEKNIK CLOZE SEBAGAI SALAH SATU TEKNIK PEMBELAJARAN KETERAMPILAN MEMBACA SISWA - Nuria Febriyana; Rusfita Sari; Siti Rukiyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
In learning Indonesian Language and Literature, there are four skills that must be mastered by students, namely writing, reading, speaking, and listening skills. Reading skills as one of the language skills are seen as very important skills because they aim not only to improve reading skills themselves, but also to explore information as an effort for children to open up the world. Learning to read must use the right technique so that students' reading skills can improve, one of which is the cloze technique. Cloze technique is a technique of removing words contained in a reading text. The use of the cloze technique can be used to train students' reading abilities and skills. Through the cloze technique, students are stimulated to be able to fill in the missing words with the appropriate words. It is hoped that with this cloze technique, students are more provoked to read word for word. Indirectly, the practice of using the cloze technique will also raises curiosity and seriousness in student when they looking for words to complete missing sentences, so that they will read the text repeatedly and train children's grasping power in understanding a text. Keywords: learning techniques, cloze techniques, reading skills.